2011
DOI: 10.1039/c1em10240k
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, sources, solubility, and transport of aerosol trace elements in a tropical region

Abstract: Aerosol particle samples (PM10) were collected at urban, industrial and rural sites located in Rio de Janeiro, Brazil, between October 2008 and September 2009. Aerosol samples for each site were analyzed for total and soluble metals, water-soluble ions, carboxylic acids, and water-soluble organic carbon (WSOC). The results showed that the mean PM10 concentrations were 34 μg m(-3); 47 μg m(-3) and 71 μg m(-3) at the rural, urban and industrial sites, respectively. An increase in the average concentration of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 20 publications
3
20
0
3
Order By: Relevance
“…[32][33][34][35][36][37][38] For example, Vasconcellos et al 39 recently performed a comparative study of the atmospheric chemical composition of Bogotá, Buenos Aires and São Paulo Cities and found that samples from São Paulo showed the highest concentrations of species analyzed on PM 10 (n-alkanes, water-soluble ions, polycyclic aromatic hydrocarbon, metals and metalloids) among all the sites. Also, Gioda et al 40 performed studies concerning chemical composition, sources, solubility and transport of aerosol trace elements in Rio de Janeiro City. Although these large urban areas concentrate a large portion of population, investigations on urban cities with potential to become a large urban conglomeration as well as rural sites (typically used for grain cultivation) are very important since they contribute with information to understand the impacts of anthropic activities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35][36][37][38] For example, Vasconcellos et al 39 recently performed a comparative study of the atmospheric chemical composition of Bogotá, Buenos Aires and São Paulo Cities and found that samples from São Paulo showed the highest concentrations of species analyzed on PM 10 (n-alkanes, water-soluble ions, polycyclic aromatic hydrocarbon, metals and metalloids) among all the sites. Also, Gioda et al 40 performed studies concerning chemical composition, sources, solubility and transport of aerosol trace elements in Rio de Janeiro City. Although these large urban areas concentrate a large portion of population, investigations on urban cities with potential to become a large urban conglomeration as well as rural sites (typically used for grain cultivation) are very important since they contribute with information to understand the impacts of anthropic activities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Photochemical processes associated with the decomposition organic species, e.g., HC, are important secondary sources. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] The formaldehyde/acetaldehyde ratios were compared with those cited in the literature 37 and the results were consistent. The lowest average rate in this study was 0.7 for B5.…”
Section: Aldehydesmentioning
confidence: 64%
“…Filters containing PM were extracted with 3.00 mL of bidistilled nitric acid, digested for 2 hours at 95 °C and cooled to 20-25 °C. 25 Then, the extracts were centrifuged to separate insoluble particles and diluted with ultrapure water. The metals quantified in the extracts were Al, V, Cr, Mn, Fe, Ni, Cu, Zn, Ga, Cd, Sb, Pb, Ti, Ba, Na, Mg, Ca, Co, and K. Calibration solutions were prepared from multielement standard solutions 1000 µg L .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, urban areas, such as Rio de Janeiro, suffer from PM air pollution (Gioda et al, 2011;Käffer et al, 2011). Researchers have employed biomonitoring by herbs to assess source apportionment, such as biomass burning (Giodarmo et al, 2013;García et al, 2009).…”
Section: Introductionmentioning
confidence: 98%